Polyurethane elastomer and polyurethane molded body
Patent Information
- Application Number
- JP2024134221
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-28
- Filing Date
- 2024-08-09
- Publication Date
- 2025-03-12
AI Technical Summary
【0010】 本開示の少なくとも一の態様によれば、柔軟でありながら、圧縮変形歪みが小さく、かつ、他部材と圧接した場合においても、他部材に滲出物を付着させることのない成形体を与えるポリウレタンエラストマーを得ることができる。また本開示の少なくとも一の態様は、柔軟でありながら、圧縮永久歪みが小さく、かつ、他部材と圧接した場合においても他部材に滲み出し物を付着させることのない成形体を得ることができる。
Smart Images

Figure 2025032984000012 
Figure 2025032984000013 
Figure 2025032984000014
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a polyurethane elastomer and a polyurethane molded article. [Background technology]
[0002] Polyurethane elastomers are used in a wide range of applications, including artificial leather, synthetic leather, paints, coating agents, adhesives, etc. In general, polyurethane elastomers are made from the reaction product of polyisocyanate and polyol, and are composed of hard segments derived from the polyisocyanate and soft segments derived from the polyol. Polyols, which are one of the raw materials for polyurethane elastomers, are classified into polyether polyols, polyester polyols, polycarbonate polyols, etc., depending on the difference in molecular chain structure, and the type of polyol is selected according to the required performance. Among them, polyurethane elastomers having a polycarbonate structure made from polycarbonate polyols have excellent abrasion resistance. In addition, they are known to be superior in heat resistance, weather resistance, hydrolysis resistance, etc., compared to polyurethane elastomers having a polyether structure or polyester structure.
[0003] On the other hand, in polyurethane elastomers having a polycarbonate structure, strong intermolecular forces act between the polycarbonate structures, causing a significant increase in hardness of the polyurethane elastomer, making it difficult to apply the polyurethane elastomer having a polycarbonate structure to applications requiring low hardness.
[0004] Patent Document 1 discloses a polyurethane elastomer that includes a matrix phase and a domain phase dispersed in the matrix phase, the matrix phase having a repeating structural unit derived from a polycarbonate diol, and the domain phase having a repeating structural unit derived from a polyether. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2022-168829 A Summary of the Invention [Problem to be solved by the invention]
[0006] The polyurethane elastomer according to Patent Document 1 can achieve both low hardness and abrasion resistance comparable to silicone elastomers, as well as low hardness and low compression set. However, the present inventors have found that when a molded body containing the polyurethane elastomer is applied to a member that is expected to be in contact with another member for a long period of time in a compressed state, such as a gripper of a robot chuck, a substance exuded from the molded body may adhere to the contacting object.
[0007] At least one aspect of the present disclosure is directed to providing a polyurethane elastomer that provides a molded article that is flexible yet has a small compression set, and that does not cause exudates to adhere to other members even when pressed against the other members. At least one aspect of the present disclosure is directed to providing a molded article that is flexible yet has a small compression set, and that does not cause exudates to adhere to other members even when pressed against the other members. [Means for solving the problem]
[0008] According to at least one aspect of the present disclosure, A polyurethane elastomer having a matrix and a plurality of domains dispersed in the matrix, In a first molded body made of the polyurethane elastomer and having a cubic shape with each side measuring 100 μm, The number N of the included domains is 10 to 77,000, the arithmetic average value Da of the equivalent sphere diameter of the domains is 1.0 to 30.0 μm; a ratio V of the total volume of the domain in the first molded body is 15 to 45 volume %, The relationship between a parameter A indicating the viscoelastic term of the domain and a parameter B indicating the viscoelastic term of the matrix, which is measured in a viscoelastic image by a scanning probe microscope of a cut section parallel to one surface of the first molded body, is as follows: A <Bであり、 The second molded body made of the polyurethane elastomer has a micro rubber hardness of 20 to 50 degrees at a temperature of 23°C, and In an indentation test of the second compact using a nanoindenter at a temperature of 23°C, a Vickers indenter is pressed into the second compact at a loading rate of 10 mN / 30 seconds, the load of 10 mN is maintained for 60 seconds, and then the load is released. The strain 5 seconds after the load is released is 1.0 μm or less. The third molded product made of the polyurethane elastomer is subjected to Soxhlet extraction in accordance with Japanese Industrial Standards (JIS) K6229:2015 using acetone as an extraction solvent at an extraction temperature of 80°C for an extraction time of 4 hours, and the ratio of the mass of the obtained extract E1 to the mass of the third molded product is defined as C (mass%); When powder of the third molded body having a mode diameter of less than 1 μm is subjected to Soxhlet extraction in accordance with Japanese Industrial Standards (JIS) K6229:2015 using acetone as an extraction solvent at an extraction temperature of 80° C. for an extraction time of 4 hours, the ratio of the mass of the obtained extract E2 to the mass of the powder is defined as D (mass%), and a polyurethane elastomer having a D / C of 1.0 to 5.0 is provided.
[0009] According to at least one embodiment of the present disclosure, there is provided a polyurethane molded article comprising the polyurethane elastomer of the present disclosure. Effect of the Invention
[0010] According to at least one aspect of the present disclosure, it is possible to obtain a polyurethane elastomer that provides a molded article that is flexible, has a small compression set, and does not cause exudates to adhere to other members even when pressed against the other members. Also, at least one aspect of the present disclosure provides a molded article that is flexible, has a small compression set, and does not cause exudates to adhere to other members even when pressed against the other members. [Brief description of the drawings]
[0011] [Figure 1] 4A to 4C are explanatory diagrams illustrating deformation of a urethane elastomer according to the present disclosure. [Diagram 2] FIG. 1 is a schematic diagram illustrating a method for producing a urethane elastomer according to one embodiment of the present disclosure. [Diagram 3] FIG. 1 is a schematic diagram illustrating a method for producing a urethane elastomer according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In this specification, the description of "XX or more and YY or less" or "XX to YY" representing a numerical range means a numerical range including the lower limit and the upper limit, which are the endpoints, unless otherwise specified. In addition, when a numerical range is described in stages, the upper limit and the lower limit of each numerical range can be arbitrarily combined. In addition, in this disclosure, for example, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ. In addition, when XX is a group, multiple XXs may be selected, and the same applies to YY and ZZ.
[0013] In order to evaluate the degree of exudation from the molded body of the polyurethane elastomer according to Patent Document 1, the present inventors conducted a solvent extraction test on a polyurethane elastomer having a matrix and a plurality of domains dispersed in the matrix. That is, a molded body of the polyurethane elastomer according to Patent Document 1, 25 mm long, 10 mm wide, and 2 mm thick, was subjected to Soxhlet extraction in accordance with Japan Industrial Standards (JIS) K6229:2015, using acetone as an extraction solvent, at an extraction temperature of 80°C, and for an extraction time of 4 hours, and the ratio of the mass of the extract obtained to the mass of the molded body (hereinafter also referred to as the solvent extraction rate) C was evaluated. It was thought that if the solvent extraction rate C was small, the exudation from the molded body would be small and adhesion to the contact object could be reduced. As a result, the solvent extraction rate C from the molded body of the polyurethane elastomer according to Patent Document 1 was sufficiently small. However, as described above, when the molded body of the polyurethane elastomer according to Patent Document 1 was maintained in contact with another object for a long period of time, adhesion to the other object could be caused by exudation.
[0014] Next, the inventors subjected the powder obtained by pulverizing the polyurethane elastomer molded body according to Patent Document 1 to a mode diameter of 1 μm or less to a solvent extraction test in the same manner as above to evaluate the ratio of the mass of the extract to the mass of the powder (solvent extraction rate D). As a result, the solvent extraction rate D of the obtained powder was approximately half of the mass of the components constituting the domains of the molded body. From this, it was found that the exudate observed from the molded body of the polyurethane elastomer according to Patent Document 1 when the molded body was kept in a compressed state for a long period of time was mainly derived from the domains. Here, the domains impart a function of reducing hardness to the polyurethane according to Patent Document 1 (paragraph 0018 of Patent Document 1).
[0015] Therefore, the present inventors have recognized that in order to address the issue of suppressing exudation from the domains of the polyurethane molded article disclosed in Patent Document 1 when the article is compressed over a long period of time, it is essential to reduce the ratio of the solvent extraction rate D to the solvent extraction rate C (hereinafter, also simply referred to as "D / C") while maintaining the high flexibility and small compression set exhibited by the polyurethane elastomer molded article disclosed in Patent Document 1.
[0016] Based on this recognition, the present inventors have conducted extensive research to reduce D / C without compromising both low hardness and abrasion resistance, and between low hardness and low compression set. As a result, they have found that a polyurethane elastomer having the following structure contributes to achieving the above object.
[0017] That is, the polyurethane elastomer according to one embodiment of the present disclosure has a matrix and a plurality of domains dispersed in the matrix. In a first molded article made of the polyurethane elastomer and having a cubic shape with one side of 100 μm, the number N of the domains contained therein is 10 to 77,000. The arithmetic average value Da of the sphere-equivalent diameters of the domains is 1.0 to 30.0 μm, the ratio V of the total volume of the domains to the first molded article is 15 to 45 vol%, and the relationship between a parameter A indicating the viscoelastic term of the domains and a parameter B indicating the viscoelastic term of the matrix, which are measured in a viscoelastic image by a scanning probe microscope of a cut surface parallel to one surface of the first molded article, is A <Bである。 In addition, the second molded body made of the polyurethane elastomer has a micro rubber hardness of 20 to 50 degrees at a temperature of 23°C, and in an indentation test using a nanoindenter at a temperature of 23°C, a Vickers indenter is pressed into the second molded body at a loading rate of 10 mN / 30 seconds, the load of 10 mN is maintained for 60 seconds, and then the load is removed, and the distortion 5 seconds after removal of the load is 1.0 μm or less. Furthermore, the third molded body made of the polyurethane elastomer is In accordance with K6229:2015, the Soxhlet extraction was performed using acetone as the extraction solvent at an extraction temperature of 80°C for 4 hours. The weight of the third molded body was calculated based on the weight of the third molded body. The mass ratio of the extracted extract E1 is C (mass%). When a powder of the third molded body having a mode diameter of less than 1 μm is subjected to Soxhlet extraction in accordance with Japanese Industrial Standards (JIS) K6229:2015 using acetone as an extraction solvent at an extraction temperature of 80°C for an extraction time of 4 hours, the ratio of the mass of the obtained extract E2 to the mass of the powder is D (mass%), and D / C is 1.0 to 5.0.
[0018] The polyurethane elastomer and the like of the present disclosure will be described in detail below with reference to preferred embodiments and drawings. Note that the embodiments described below are merely examples, and the present disclosure is not limited to these embodiments unless otherwise specified.
[0019] The polyurethane elastomer satisfies the following requirements (1-1) to (1-4). Requirement (1-1): The material has a matrix and a plurality of domains dispersed in the matrix. Requirement (1-2): The relationship between parameter A indicating the viscoelasticity term of the domain and parameter B indicating the viscoelasticity term of the matrix, which is measured in a viscoelastic image of a cross section parallel to one face of a first molded body having a cubic shape with a side length of 100 μm and made of a polyurethane elastomer, by a scanning probe microscope, is A <Bである。 That is, in a cut surface parallel to one surface of the molded article, a matrix domain structure of the polyurethane elastomer is observed, and the elastic modulus of the polyurethane elastomer matrix observed in the cut surface is greater than the elastic modulus of the domain.
[0020] Requirement (1-3): The second molded body made of a polyurethane elastomer has a micro rubber hardness of 20 to 50 degrees at a temperature of 23°C. Requirement (1-4): In an indentation test of the second molded body using a nanoindenter at 23°C, a Vickers indenter is pressed into the second molded body at a loading rate of 10 mN / 30 seconds, the load of 10 mN is maintained for 60 seconds, and then the load is released. The distortion 5 seconds after the load is released is 1.0 μm or less.
[0021] In polyurethane elastomers, the matrix is responsible for the function of recovery from deformation, and the domain is responsible for reducing the hardness of the polyurethane elastomer. Such polyurethane elastomers exhibit softness and quick recovery from deformation. On the other hand, general polyurethane elastomers also have a difference in elastic modulus between the so-called hard segment and soft segment. However, in general polyurethane elastomers, the soft segment constitutes the matrix and the hard segment constitutes the domain, and it is believed that there has been no polyurethane elastomer that exhibits the fast recovery speed from deformation specified in the requirement (1-4) while having the flexibility specified in the above requirement (1-3).
[0022] FIG. 1A is a cross-sectional view of a polyurethane molded article 3 according to one embodiment of the present disclosure. FIG. 1A shows a schematic diagram of a matrix 31 of a polyurethane elastomer and a plurality of domains 32 dispersed in the matrix 31, as observed on a cross section parallel to one surface of a molded article. As described above, the polyurethane elastomer has a matrix 31 and domains 32 dispersed in the matrix. That is, the polyurethane elastomer has a matrix-domain structure. The matrix exhibits higher elasticity than the domains.
[0023] 1A and 1B are explanatory diagrams of the deformation recovery property of a polyurethane molded body 3 according to one embodiment of the present disclosure. As shown in FIG. 1A, a plurality of domains 32 are dispersed in a matrix 31. Since the domains 32 have a lower elasticity than the matrix 31, the polyurethane When the molded body 3 is compressed in the direction of the arrow F as shown in FIG. 1B, the domains 32 are preferentially deformed. Therefore, even if the matrix 31 has high elasticity, the micro rubber hardness of the polyurethane molded body can be reduced. Furthermore, when the polyurethane molded body is released from compression, the elasticity of the matrix 31, which is the continuous phase, allows the thickness of the molded body to quickly return to the thickness before compression.
[0024] (Number of domains N) In the first molded article made of the polyurethane elastomer and having a cubic shape with one side of 100 μm, the number N of the domains contained in the first molded article is 10 to 77,000. The number N of the domains can be 100 to 77,000, or can be 700 to 77,000. When the number N of the domains is within the above range, a polyurethane elastomer that is flexible but has a small compressive deformation strain can be obtained. The number N of the domains can be adjusted by the mixing conditions (shear force and time) during the preparation of the urethane prepolymer and the molecular weight and amount of the polyol and polyisocyanate added. The number of domains N can be determined by three-dimensional measurement of the first molded body using FIB-SEM. The first molded body may be a heat-cured polyurethane elastomer as is, or the heat-cured polyurethane elastomer may be processed into a predetermined shape using a microtome to obtain the first molded body.
[0025] FIB-SEM is a technique in which a sample is processed using a FIB (Focused Ion Beam) device, and the exposed cross section of the sample is observed using a SEM (scanning electron microscope). To examine the three-dimensional structure, a large number of photographs are taken by repeating successive processing and observations, and then these SEM images are subjected to 3D reconstruction processing using computer software. The three-dimensional structure of the sample can then be examined by constructing a three-dimensional image of the sample. As a specific method for measuring the number N of domains, a FIB-SEM (manufactured by FEI) is used to obtain three-dimensional stereoscopic images of the first molded body at intervals of 60 nm. Then, the number N of domains is calculated for the obtained images using 3D visualization and analysis software Avizo (registered trademark, manufactured by FEI). A more specific measurement method will be described later.
[0026] (arithmetic mean value of the equivalent spherical diameter of the domain Da) In the first molded body made of the polyurethane elastomer and having a cubic shape with a side length of 100 μm, the arithmetic mean value Da of the sphere-equivalent diameter of the domain is 1.0 to 30.0 μm. The arithmetic mean value Da may be 2.0 to 20.0 μm, or 2.0 to 15.0 μm. When the arithmetic mean value Da is in the above range, a polyurethane elastomer that is flexible but has a small compressive deformation strain can be obtained. The arithmetic mean value Da can be adjusted by the mixing conditions (shear force and time) during preparation of the urethane prepolymer, and the molecular weight and amount of polyol and polyisocyanate added. The arithmetic mean value Da can be determined by three-dimensional measurement of the first molded body using the above-mentioned FIB-SEM. A specific measurement method will be described later.
[0027] (Proportion V of the total volume of the domain in the first compact) In a first molded article made of the polyurethane elastomer and having a cubic shape with one side of 100 μm, the ratio V of the total volume of the domains in the first molded article is 15 to 45 volume %. The ratio V of the total volume of the domains in the first molded article may be 20 to 45 volume %, or 25 to 42 volume %, and is preferably 25 to 41 volume %. When the ratio V of the total volume of the domains in the first molded article is in the above range, a polyurethane elastomer that is flexible yet has small compression deformation distortion can be obtained. The ratio V of the total volume of the domains in the first molded article can be adjusted depending on the mixing conditions (shear force and time) during preparation of the urethane prepolymer and the like. It can be adjusted by the molecular weight and amount of polyol and polyisocyanate added. The ratio of the total volume of the domains in the first molded body can be determined by the three-dimensional measurement of the first molded body using the above-described FIB-SEM. Specific measurement methods will be described later.
[0028] (Parameter indicating viscoelastic term) In a first molded body in the shape of a cube with a side length of 100 μm made of a polyurethane elastomer, in the viscoelastic image of a cross-sectional plane parallel to one surface of the first molded body measured by a scanning probe microscope, the parameter A indicating the viscoelastic term of the domain and the parameter B indicating the viscoelastic term of the matrix satisfy A < B. That is, the elastic modulus of the matrix of the polyurethane elastomer observed in the cross-sectional plane is greater than the elastic modulus of the domain. Thereby, it becomes easier to achieve both hardness and recovery of deformation. The difference in the relative elastic moduli of the matrix 31 and the domain 32 can be determined by thinning the first molded body and measuring it with a scanning probe microscope (SPM / AFM). As the scanning probe microscope, for example, "S-Image" (trade name) manufactured by Hitachi High-Technologies Corporation can be used. Further, as means for thinning, for example, a sharp razor, a microtome, a focused ion beam method (FIB), etc. can be mentioned, but in the present disclosure, a microtome is used. The location where the section is made is an arbitrary cross-sectional plane parallel to one surface of the first molded body in the shape of a cube with a side length of 100 μm. The observation region of the viscoelastic image in the cross-sectional plane is an arbitrary region of 50 μm square.
[0029] The measurement mode for the viscoelastic image using SPM is the micro-viscoelastic dynamic force mode (VE-DFM). The cantilever used is a silicon micro-cantilever for DMF ("SI-DF3" (product name), Hitachi High-Tech Science Corporation, spring constant = 1.9 N / m). The scanning frequency is 0.5 Hz. VE-DFM is one of the measurement modes of SPM (scanning probe microscope). In VE-DFM, a surface topography image can be obtained by controlling the distance between the probe and the measurement sample so that the vibration and amplitude of the cantilever are constant while the cantilever is resonating.
[0030] After acquiring a viscoelastic image, the parameters indicating the viscoelastic term in each observation region are obtained for 10 points each for the matrix and domain, and their arithmetic mean values are taken as parameter A indicating the viscoelastic term of the domain and parameter B indicating the viscoelastic term of the matrix. Note that the units of parameters A and B are mV, and the larger the value, the higher the elasticity.
[0031] The ratio (A / B) of parameter A to parameter B is preferably 0.65 or less, may be 0.50 or less, or may be 0.40 or less. The smaller A / B is, the greater the difference in viscoelasticity between the matrix and the domain, making it easier to achieve both hardness and recovery from deformation. There is no particular limit to the lower limit of A / B, but the smaller the value, the more preferable. Specifically, for example, it is 0.10. For example, A / B is preferably 0.10 to 0.65, 0.10 to 0.50, or 0.10 to 0.40. The parameters A and B can be adjusted, for example, by changing the elastic modulus of the domain and the matrix. The elastic modulus of the matrix can be adjusted by the molecular weight, bonding species, and added amount of the polyol or polyisocyanate. The elastic modulus of the domain can be adjusted by the molecular weight, bonding species, and added amount of the polyol or polyisocyanate, or by adding a chain extender such as a polyhydric alcohol. The value of parameter A is not particularly limited, but may be, for example, 50 to 120 mV, or 60 to 110 mV. The value of parameter B is not particularly limited, but may be, for example, 190 to 310 mV, or 210 to 290 mV.
[0032] (Micro rubber hardness of molded body) The second molded body made of polyurethane elastomer has a micro rubber hardness of 20 to 50 degrees at a temperature of 23°C. Here, the second molded body is a cubic molded body with one side of 2 mm. If the thickness of the sample is less than 2 mm, the second molded body is stacked in the thickness direction to form a cubic second molded body with one side of 2 mm. By having a micro rubber hardness of 50 degrees or less, flexibility is good and hardness is low. By having a micro rubber hardness of 20 degrees or more, mechanical strength is high and abrasion resistance is good. The micro rubber hardness is preferably 25 to 50 degrees, and more preferably 30 to 50 degrees. The micro rubber hardness can be adjusted by the elastic modulus of the matrix, the ratio of the matrix to the domain, etc. Specifically, for example, increasing the elastic modulus of the matrix acts in the direction of increasing the micro rubber hardness. The micro rubber hardness is determined as follows. The measurement point is the approximate center of any one face of the cubic second molded body with a side length of 2 mm, and the micro rubber hardness is measured at a temperature of 23°C using a micro rubber hardness meter (product name: MD-1capa; manufactured by Kobunshi Keiki Co., Ltd., indenter: type A (cylindrical, diameter 0.16 mm, height 0.5 mm, outer diameter 4 mm, inner diameter 1.5 mm), measurement mode: peak hold mode). When the thickness of the sample is less than 2 mm, the measurement point is the approximate center of one face of the second molded body that can measure the micro rubber hardness from the thickness direction of the sample of the second molded body. Moreover, the heat-cured polyurethane elastomer may be used as it is for the second molded body, or the heat-cured polyurethane elastomer may be processed into a predetermined shape using scissors to form the second molded body.
[0033] (Recovery from deformation) In an indentation test using a nanoindenter at a temperature of 23°C of a second molded body made of a polyurethane elastomer, a Vickers indenter is pressed into the second molded body at a loading rate of 10 mN / 30 seconds, and the load of 10 mN is maintained for 60 seconds, and then the load is released. The strain after 5 seconds of release is 1.0 μm or less. The strain after 5 seconds of release is preferably 0.8 μm or less, more preferably 0.7 μm or less, and even more preferably 0.6 or less. The lower limit of the strain after 5 seconds of release is not particularly limited, but is usually 0.0 μm, and may be 0.1 μm. For example, preferred examples include 0.0 to 1.0 μm, 0.0 to 0.8 μm, 0.0 to 0.7 μm, and 0.1 to 0.6 μm. By setting the strain 5 seconds after unloading within the above range, a polyurethane elastomer exhibits a fast recovery rate from deformation. The strain after 5 seconds of unloading can be adjusted by the type of resin in the matrix, the number of domains, and the domain size.
[0034] The value of the strain 5 seconds after unloading is obtained as follows. The measurement point is approximately the center of any one face of the cubic second compact with a side length of 2 mm, and a pressing test is performed at a temperature of 23°C using a nanoindenter (product name: Fischerscope HM2000, manufactured by Fisher Instruments Co., Ltd., a Vickers indenter with a square pyramid shape and a facing angle of 136°). The Vickers indenter is pressed into the second compact at a loading rate of 10 mN / 30 seconds, and the load of 10 mN is maintained for 60 seconds. Thereafter, the load is removed at a loading rate of 10 mN / 30 seconds, and the value of the strain 5 seconds after unloading is measured. Moreover, the heat-cured polyurethane elastomer may be used as it is for the second molded body, or the heat-cured polyurethane elastomer may be processed into a predetermined shape using scissors to form the second molded body.
[0035] (Solvent extraction rate C and powder solvent extraction rate D) The third molded body made of the polyurethane elastomer was subjected to soaking in acetone as an extraction solvent at 80°C for 4 hours in accordance with JIS K6229:2015. The ratio of the mass of the obtained extract E1 to the mass of the third molded body when subjected to the Xhlet extraction is defined as C (mass%); The powder of the third molded body having a mode diameter of less than 1 μm is subjected to Soxhlet extraction in accordance with JIS K6229:2015 using acetone as an extraction solvent at an extraction temperature of 80° C. for an extraction time of 4 hours. When the ratio of the mass of the obtained extract E2 to the mass of the powder is defined as D (mass%), D / C is 1.0 to 5.0. Here, the third molded body is a molded body having a length of 25 mm, a width of 10 mm, and a thickness of 2 mm. Moreover, D / C is preferably 1.5 to 4.5, and more preferably 1.5 to 3.0. As described above, by setting D / C within the above range, it is possible to obtain a polyurethane elastomer which is flexible yet has small compressive deformation strain and which gives a molded article that does not cause exudates to adhere to other members even when pressed against the other members. D / C can be adjusted by adjusting the value of C or the value of D, as described below.
[0036] (Solvent extraction rate C) The solvent extraction rate C of the polyurethane elastomer is determined by Soxhlet extraction. First, the polyurethane elastomer is molded into a molded body using a mold for making a 2 mm thick sheet. Then, the molded body is cut with scissors into a length of 25 mm, a width of 10 mm, and a thickness of 2 mm to obtain the third molded body. If the thickness of the sample is less than 2 mm, prepare a number of samples that will be 2 mm when stacked, and stack the samples to obtain a thickness of 2 mm. Then, in accordance with Japanese Industrial Standards (JIS) K6229:2015, the third molded body is subjected to Soxhlet extraction using acetone as the extraction solvent, at an extraction temperature of 80°C, and for an extraction time of 4 hours. The ratio of the mass of the obtained extract E1 to the mass of the third molded body is calculated as the solvent extraction rate C (mass%).
[0037] The value of the solvent extraction rate C is not particularly limited, but is preferably 2.2 to 4.5 mass%, more preferably 2.3 to 3.5 mass%, and even more preferably 2.3 to 3.0 mass%. By being in the above range, it becomes easier to set the value of D / C in the above range. The value of the solvent extraction rate C can be adjusted by the type and amount of catalyst added, and the type of matrix resin.
[0038] (Solvent extraction rate of powder D) The solvent extraction rate D of the powder is determined by Soxhlet extraction. First, the polyurethane elastomer is molded into a 2 mm thick sheet using a mold. The molded body is then cut into a length of 25 mm, width of 10 mm, and thickness of 2 mm using scissors to obtain the third molded body. The third molded body is crushed while sandwiched between filter paper to obtain a powder, and the solvent extraction rate D of the powder is determined in the same manner as the solvent extraction rate C described above. Examples of crushing methods include freeze crushing and crushing by pressing, but crushing by pressing using filter paper is preferred because it is easy to extract viscous materials. As a specific pulverization method, the above-mentioned third molded body is sandwiched between two sheets of Kiriyama funnel filter paper 5B, which is then sandwiched between two degreased aluminum sheets, and pressed for 1 minute at 10 MPa using a 50-ton press (product name: PEF 5041, manufactured by Kansai Roll Co., Ltd.) preheated to 130° C. After unloading, the aluminum sheets are removed, and the two sheets of Kiriyama funnel filter paper sandwiching the pulverized third molded body are folded together and placed in a Soxhlet cylindrical filter paper, and the solvent extraction rate D of the powder is determined in the same manner as the solvent extraction rate C described above.
[0039] To determine the mode diameter of a powder, a laser diffraction / scattering type particle size distribution analyzer is used because it can be used in dry conditions and allows for easy measurement. Specifically, the particle size distribution is measured using a laser diffraction / scattering type particle size distribution measuring device (product name: Partica LA-960V2, manufactured by Horiba, Ltd.) equipped with a dry measurement unit, and the particle size distribution is determined to have the maximum peak (mode diameter). The mode diameter is the size of the ground material. show.
[0040] The value of the solvent extraction rate D of the powder is not particularly limited, but is preferably 3.0 to 20.0 mass%, more preferably 4.0 to 17.0 mass%, further preferably 4.3 to 11.0 mass%, and particularly preferably 4.3 to 7.0 mass%. By being in the above range, it becomes easier to set the value of D / C in the above range. The value of the solvent extraction rate D of the powder can be adjusted by the type and amount of a chain extender such as a polyhydric alcohol or a catalyst.
[0041] The number average molecular weight of the extract E2 obtained by Soxhlet extraction of the powder obtained by the same method as the solvent extraction rate D of the powder is preferably 2,000 to 100,000, more preferably 2,500 to 100,000, and even more preferably 5,000 to 100,000. By being in the above range, a polyurethane elastomer that is flexible but has a small compression deformation strain can be obtained. In addition, the number average molecular weight of the extract E2 can be adjusted by changing the material that constitutes the domain. The method for measuring the number average molecular weight of the extract E2 will be described later. The number average molecular weight of extract E2 may be, for example, 2,000 to 50,000, or may be 25,000 to 30,000.
[0042] The viscosity of extract E2 obtained by Soxhlet extraction of the powder obtained by the same method as the solvent extraction rate D of the powder is preferably 10,000 mPa·s or less. The lower limit is not particularly limited, but for example, it is preferably 1,000 to 10,000 mPa·s, more preferably 1,200 to 10,000 mPa·s, and even more preferably 2,000 to 10,000 mPa·s. By being in the above range, a polyurethane elastomer that is flexible but has a small compression deformation strain can be obtained. In addition, the viscosity of extract E2 can be adjusted by changing the material that constitutes the domain. The method for measuring the viscosity of extract E2 will be described later.
[0043] (Wear resistance) When a ball-on-disk abrasion test is performed on the surface in the thickness direction of a sheet-like abrasion test piece made of polyurethane elastomer, measuring 30 mm in length, 30 mm in width, and 2 mm in thickness, in accordance with JIS R1613:2010 under the following conditions (1) to (6), the mass loss rate of the abrasion test piece is preferably 10.0% by mass or less, more preferably 5.0% by mass or less, even more preferably 2.0% by mass or less, even more preferably 1.0% by mass or less, and particularly preferably 0.5% by mass or less. By being in the above range, the abrasion resistance is good.
[0044] (1) Ball Material: Stainless steel Diameter: 10mm (2) Load: 100g (3)Environment: Temperature 23℃, 50%RH (4) Time: 60 minutes (5) Sliding circle diameter: 10 mm (6) Rotation speed of the disk on which the test specimen is placed: 300 rpm.
[0045] The wear test is carried out as follows. First, the mass of the wear test piece is measured. Next, the wear test piece is fixed with double-sided tape so that the center of the wear test piece is positioned approximately at the center of the sliding disk of a ball-on-disk friction and wear tester (product name: HEIDON Type: 20, manufactured by Shinto Chemical Co., Ltd.). At this time, the surface in the thickness direction of the wear test piece is placed in contact with the sliding disk. Next, the indenter made of the ball is pressed against the center of the wear test piece with a load of 100 g, and the wear test piece is rotated and slid for 60 minutes with a sliding circle diameter of 10 mm and a rotation speed of 300 rpm. After 60 minutes, the test piece is stopped, the wear powder and the double-sided tape are removed, and the mass of the test piece is measured. The mass reduction rate (mass%) is calculated from the mass of the test piece before and after the wear test. Here, the surface in the thickness direction of the wear test piece refers to a 30 mm square surface of the wear test piece that is 30 mm long and 30 mm wide. The mass loss rate of the abrasion test specimen can be adjusted by the type of resin in the matrix, the number of domains, and the size of the domains.
[0046] (Polyurethane elastomer material) The polyurethane elastomer material will now be described. As described above, the polyurethane elastomer has a matrix 31 and a plurality of domains 32 dispersed in the matrix. That is, the polyurethane elastomer has a matrix domain structure. It is preferable that the matrix 31 has a structure capable of increasing the deformation recovery speed, and the domain 32 has a structure that contributes to suppressing an increase in micro rubber hardness.
[0047] Such a polyurethane elastomer matrix 31 preferably has a first structure (polycarbonate structure) represented by formula (1). The matrix has at least one polycarbonate structure represented by formula (1), and preferably has a plurality of polycarbonate structures. When the matrix has a plurality of polycarbonate structures represented by formula (1), the polycarbonate structures can be repeating structural units. In addition, R in the first structure represented by formula (1) 1 The alkylene group having 3 to 9 carbon atoms represented by the following formula may have a linear structure or a branched structure, but more preferably has a branched structure. [ka] (In formula (1), R 1 represents an alkylene group having 3 to 9 carbon atoms (preferably 6 to 9).
[0048] Polyurethane obtained by reacting a polyol having a polycarbonate structure (polycarbonate polyol) with a polyisocyanate exhibits high elasticity due to the strong intermolecular force between carbonate groups, and is therefore preferable as a component of the matrix 31. Also, R 1is an alkylene group having 3 to 9 carbon atoms, incompatibility with the domain containing the second structure (polyether structure) represented by the following formula (2) described later is ensured, and the matrix and the domain can be clearly phase-separated. This makes it possible to more reliably exhibit the two functions of the polyurethane elastomer, namely softness and fast recovery from deformation. Also, R 1 When is an alkylene group having a branched structure and having 3 to 9 carbon atoms, the intermolecular force between the carbonate groups can be appropriately suppressed, and the matrix can be prevented from becoming excessively high in elasticity.
[0049] R 1 For example, -(CH2) m -(m=3 to 9, preferably 6 to 9), -CH2C(CH3)2CH2-, -CH2CH(CH3)CH2-, -(CH2)2CH(CH3)(CH2)2-, etc. These can be used alone or in combination of two or more.
[0050] The number average molecular weight of the polycarbonate and the polyols described below can be calculated by the following formula using the hydroxyl value (mgKOH / g) and valence. For example, the number average molecular weight of a polyether polyol with a hydroxyl value of 56.1 mgKOH / g and a valence of 2 can be calculated to be 2000. Number average molecular weight = 56.1 x 1000 x valence ÷ hydroxyl value
[0051] The elastic modulus of the matrix can be adjusted by, for example, a method of increasing the crosslink density using a trimer compound or polymer compound of polyisocyanate. Normally, increasing the elastic modulus also increases the micro rubber hardness of the polyurethane elastomer, but in the present disclosure, multiple low elastic domains are dispersed in the matrix, so that excessive hardness can be suppressed.
[0052] The domain 32 preferably contains a second structure (polyether structure) represented by formula (2). The domain has at least one polyether structure represented by formula (2), and preferably has a plurality of polyether structures represented by formula (2). When the domain has a plurality of polyether structures represented by formula (2), the polyether structures can be repeating structural units. In addition, R in the structural unit represented by formula (2) 2 The alkylene group having 3 to 6 carbon atoms represented by the following formula may have a linear structure or a branched structure, but more preferably has a branched structure. [ka] (In formula (2), R 2 represents an alkylene group having 3 to 6 carbon atoms (preferably 3 to 4 carbon atoms).
[0053] Polyethers exhibit low elastic modulus due to weak intermolecular forces between ether groups, making them a preferred component of domains. Also, R 2 is an alkylene group having 3 to 6 carbon atoms, which ensures incompatibility with the matrix having the polycarbonate structure represented by formula (1) and results in clear phase separation between the matrix and the domain, which is preferable.
[0054] R 2 For example, -(CH2) m -(m=3 to 6), -CH2CH(CH3)-, -CH2C(CH3)2CH2-, -CH2CH(CH3)CH2-, -(CH2)2CH(CH3)CH2-, etc. These can be used alone or in combination of two or more.
[0055] The number average molecular weight of the polyether structure represented by formula (2) is preferably 1000 to 50000. More preferably, it is 1200 to 30000. When the number average molecular weight is 1000 or more, the incompatibility between the domain and the matrix containing the polycarbonate structure represented by formula (1) becomes better, and the phase separation between the matrix and the domain becomes clear, which is preferable. Also, when the number average molecular weight is 50000 or less, the domain is easily formed, and the phase separation form is stabilized, which is preferable.
[0056] The domain preferably has a third structure, and the third structure is formed by addition polymerization of at least one selected from the group consisting of ethylene oxide and propylene oxide to glycerin. That is, the third structure is preferably an addition polymer of glycerin and at least one selected from the group consisting of ethylene oxide and propylene oxide. When the domain has the third structure, the three-branched structure derived from glycerin forms a three-dimensional crosslinked structure. By taking this, even if the ends are unreacted, they will entangle with the parts that are cross-linked to the matrix due to their three-dimensional expansion, and the exudation of components derived from the domains can be suppressed.
[0057] The chemical structures of the matrix and domains can be analyzed using, for example, a spectroscopic analyzer such as an AFM infrared spectroscopic analyzer, a microscopic infrared spectroscopic analyzer, or a microscopic Raman spectroscopic analyzer, or a mass spectrometer.
[0058] (Method of producing polyurethane elastomer) An example of the method for producing the above-mentioned polyurethane elastomer includes a method having the following steps (i) to (iii). Step (i): A step of reacting a first polyether having at least two isocyanate groups with a first polycarbonate polyol having at least two hydroxyl groups to obtain a urethane reactive emulsifier having at least two hydroxyl groups. Step (ii): A step of obtaining a dispersion in which droplets containing at least a portion of the urethane reactive emulsifier are dispersed in the second polycarbonate polyol. Step (iii): preparing a mixture for forming a polyurethane elastomer containing the dispersion obtained in step (ii) and a polyisocyanate having at least two isocyanate groups, and then reacting the urethane reactive emulsifier, the second polycarbonate polyol, and the polyisocyanate in the mixture for forming a polyurethane elastomer.
[0059] Each step of the above manufacturing method will be described with reference to FIG. In step (i), a first polyether 51 having at least two isocyanate groups is mixed with a first polycarbonate polyol 52 having at least two hydroxyl groups. In the presence of a catalyst, the isocyanate groups and hydroxyl groups in the mixture are reacted to link them via a urethane bond, thereby obtaining a urethane reactive emulsifier 53 having at least two hydroxyl groups. The urethane reactive emulsifier is a reactive emulsifier having a urethane bond.
[0060] In step (ii), the urethane reactive emulsifier 53 obtained in step (i) is dispersed in the second polycarbonate polyol 55. The segment derived from the first polyether 51 contained in the urethane reactive emulsifier 53 is not compatible with the second polycarbonate polyol 55 and forms droplets 54. On the other hand, in the second polycarbonate polyol 55, the droplets 54 containing the segment derived from the first polyether constituting a part of the urethane reactive emulsifier are uniformly and stably dispersed via the segment derived from the first polycarbonate polyol 52 contained in the urethane reactive emulsifier 53. As a result, a dispersion is obtained in which the droplets 54 containing the segment derived from the first polyether 51 of the urethane reactive emulsifier 53 are dispersed in the second polycarbonate polyol 55. Note that, for the sake of explanation, steps (i) and (ii) are described separately, but these steps may be a continuous series of steps.
[0061] In step (ii), the second polycarbonate polyol 55 in which the droplets 54 are dispersed can be the unreacted product of the first polycarbonate polyol used in step (i) with the first polyether. That is, in step (i), by using an excess amount of the first polycarbonate polyol relative to the first polyether, a dispersion in which the urethane reactive emulsifier 53 described in step (ii) is dispersed in the excess first polycarbonate polyol, i.e., the second polycarbonate polyol 55, can be obtained. Even when an excess amount of the first polycarbonate polyol is used, a polycarbonate polyol (second polycarbonate polyol) as a dispersion medium for the urethane reactive emulsifier can be additionally added. In this case, the polycarbonate polyol to be added may have the same chemical composition as the first polycarbonate polyol used in step (i) or may be different.
[0062] On the other hand, in step (i), the first polycarbonate polyol and the first polyether are reacted in equivalent amounts, and when the first polycarbonate polyol is completely consumed, a new polycarbonate polyol is used as the second polycarbonate polyol to prepare a dispersion in step (ii). Even in this case, the polycarbonate polyol used as the second polycarbonate polyol may have the same chemical composition as the first polycarbonate polyol or may have a different chemical composition.
[0063] Finally, in step (iii), a polyurethane elastomer forming mixture is prepared containing the dispersion prepared in step (ii) and a polyisocyanate 56 having at least two isocyanate groups. Next, the terminal hydroxyl group of the urethane reactive emulsifier 53, the hydroxyl group of the second polycarbonate polyol 55, and the isocyanate group of the polyisocyanate 56 in the polyurethane elastomer forming mixture are reacted. In this way, a network structure is formed via urethane bonds, and the polyurethane elastomer forming mixture is cured to obtain a polyurethane elastomer. The polyurethane elastomer 500 thus obtained has a matrix domain structure in which domains 32 containing polyether derived from the first polyether 51 are dispersed in a matrix 31 containing a urethane elastomer having polycarbonate derived from the first polycarbonate polyol 52 and the second polycarbonate polyol 55. Moreover, the domain 32 is mainly composed of a polyether structure, and a component that does not substantially have a crosslinked structure, i.e., a liquid component, may exist inside the domain, which allows the domain to have a low elastic modulus in the polyurethane elastomer.
[0064] Furthermore, it is believed that the domain is not simply a liquid component confined in the matrix, but that the domain and the matrix are chemically bonded to each other through urethane bonds at the boundary between the domain and the matrix, and therefore the recovery of the domain from deformation when the load applied to the polyurethane elastomer is removed can be linked to the recovery of the matrix from deformation. Here, as described above, the substantially liquid domain does not substantially have a crosslinked structure inside. Therefore, it is difficult for the domain that is deformed by the application of a load to the polyurethane elastomer to autonomously recover from the deformation. However, in the polyurethane elastomer, it is considered that the domain is chemically bonded to the matrix at the boundary portion with the matrix. This allows the domain to recover from the deformation together with the recovery of the deformation of the matrix. This achieves stable deformation (amount of deformation) and stable recovery from the deformation even when the polyurethane elastomer is repeatedly subjected to loading and unloading.
[0065] The above steps (i) to (ii) are steps for stably dispersing a polyether, which is originally difficult to disperse stably and uniformly due to its low compatibility, in a polyol. That is, the first polyether 51 is reacted with the first polycarbonate polyol 52 to obtain a urethane reactive emulsifier 53. This is a step for obtaining a dispersion in which the polyether segments derived from the first polyether 51 are stably and uniformly dispersed in the second polycarbonate polyol. This makes it easy to prepare a polyurethane elastomer in which domains 32 having a high circularity and a relatively uniform size distribution, which are small on the order of micrometers, are dispersed in the matrix 31.
[0066] As another method for mixing materials with low compatibility, for example, there is a method of mixing and dispersing them with high shearing force. However, in this method, high shearing force is applied to the polyether, which results in distorted domain shapes and reduced circularity, and the sizes of the domains may also be non-uniform. In addition, the dispersion state is unstable, and the domains disperse relatively quickly. In addition, the incompatibility between the polyether and the polycarbonate polyol is not ensured, and the phase separation between the matrix and the domain of the resulting polyurethane elastomer becomes unclear. Therefore, it is difficult to obtain a polyurethane elastomer that gives an elastic body having flexibility and excellent deformation recovery properties according to the present disclosure.
[0067] The first polyether has at least two isocyanate groups. The first polyether is preferably a polyether having a second structure represented by formula (2). The first polyether can be obtained, for example, by reacting a polyether polyol (corresponding to the "first polyol" in the examples) having at least two hydroxyl groups and the second structure represented by formula (2) with a polyisocyanate having at least two isocyanate groups. Examples of polyether polyols include polyether polyols containing an alkylene structure, such as polypropylene glycol, polytetramethylene glycol, a copolymer of tetrahydrofuran and neopentyl glycol, and a copolymer of tetrahydrofuran and 3-methyltetrahydrofuran, and random or block copolymers of these polyalkylene glycols. These may be used alone or in combination of two or more. Here, the combined use of a bifunctional polyether polyol and a trifunctional polyether polyol as the polyether polyol having at least two hydroxyl groups and the second structure represented by formula (2) is preferable in that it suppresses the exudation of substances originating from the domains onto the surface of the polyurethane elastomer molded article and makes it easier to adjust D / C within the range of 1.0 to 5.0. The reason for this will be explained with reference to FIG. 3.
[0068] When a polyether polyol having two hydroxyl groups, a polyether polyol having three hydroxyl groups, and a polyisocyanate having at least two isocyanate groups are used in combination as the polyether polyol, a first polyether 57 having three isocyanate groups at its terminals is obtained in addition to a first polyether 51 having two isocyanate groups at its terminals as a result of the reaction with the polyisocyanate having at least two isocyanate groups. In step (i), these first polyethers are reacted with a first polycarbonate polyol 52 having at least two hydroxyl groups to obtain a urethane reactive emulsifier 53 having at least two hydroxyl groups. The urethane reactive emulsifier 53 obtained here has a three-dimensional network structure. In the polyurethane elastomer obtained through the subsequent steps (ii) to (iii) using such a urethane reactive emulsifier, the amount of polyol not bound to the matrix in the domain can be reduced. For this reason, by using a bifunctional polyether polyol and a trifunctional polyether polyol in combination as the polyether polyol, the value of D can be reduced, and thus D / C can be more easily adjusted within the range of 1.0 to 5.0. As the trifunctional polyether polyol, triol-type polypropylene glycol, triol-type polyethylene glycol, and copolymers of polyethylene oxide and polypropylene oxide, which are triol-type copolymers, can be particularly preferably used. Here, for example, triol-type polypropylene glycol refers to polypropylene glycol having three hydroxy groups in the molecule.
[0069] Among the polyether polyols, amorphous polyether polyols are preferred from the viewpoints of incompatibility with the second polycarbonate polyol and of enabling low hardness to be achieved. More preferably, the liquid contains at least one selected from the group consisting of polypropylene glycol, a copolymer of tetrahydrofuran and neopentyl glycol, and a copolymer of tetrahydrofuran and 3-methyltetrahydrofuran.
[0070] The number average molecular weight of the polyether polyol is preferably 1000 to 50000. More preferably, it is 1200 to 30000. When the number average molecular weight is 1000 or more, the incompatibility with the polycarbonate polyol is ensured, and the phase separation between the matrix and the domain of the obtained urethane elastomer becomes clear, which is preferable. Also, when the number average molecular weight is 50000 or less, the domain is easily formed, and the phase separation form is stabilized, which is preferable.
[0071] Examples of polyisocyanates to be reacted with polyether polyol include pentamethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, trimer compounds (isocyanurates) of these polyisocyanates, polymer compounds, allophanate type polyisocyanates, biuret type polyisocyanates, water-dispersible polyisocyanates, etc. These polyisocyanates can be used alone or in combination of two or more kinds. Among the polyisocyanates, a bifunctional isocyanate having two isocyanate groups is preferred because of its high compatibility with the first polyether and the ease of adjusting physical properties such as viscosity. More preferably, the polyisocyanate contains at least one selected from hexamethylene diisocyanate, isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, and diphenylmethane diisocyanate. Among these, xylylene diisocyanate is even more preferred.
[0072] In the step of reacting the polyether polyol with the polyisocyanate, the isocyanate index is preferably in the range of 1.2 to 5.0. By having the isocyanate index in this range, the components derived from the first polyether remaining without being network structured can be reduced, and the exudation of liquid substances from the polyurethane elastomer can be suppressed. The isocyanate index indicates the ratio ([NCO] / [OH]) of the number of moles of isocyanate groups in the isocyanate compound to the number of moles of hydroxyl groups in the polyol compound. The first polyether obtained by the reaction of polyether polyol with polyisocyanate has a structure in which hydroxyl groups and isocyanate groups are linked via urethane bonds formed by the reaction of the hydroxyl groups and isocyanate groups. The number average molecular weight is preferably 1,000 to 50,000. More preferably, it is 1,200 to 30,000.
[0073] The first polycarbonate polyol has at least two hydroxyl groups. It is also preferable that the first polycarbonate polyol has a first structure represented by formula (1). Examples of the first polycarbonate polyol include a reaction product of a polyhydric alcohol and phosgene, and a ring-opening polymer of a cyclic carbonate ester (such as an alkylene carbonate).
[0074] Examples of polyhydric alcohols include propylene glycol, dipropylene glycol, trimethylene glycol, 1,4-tetramethylene diol, 1,3-tetramethylene diol, 2-methyl-1,3-trimethylene diol, 1,5-pentamethylene diol, neopentyl glycol, 1,6-hexamethylene diol, 3-methyl-1,5-pentamethylene diol, 2,4-diethyl-1,5-pentamethylene diol, glycerin, trimethylolpropane, trimethylolethane, cyclohexanediols (such as 1,4-cyclohexanediol), and sugar alcohols (such as xylitol and sorbitol).
[0075] Examples of alkylene carbonates include trimethylene carbonate and tetramethylene carbonate. Examples of suitable ethylene carbonate include ethylene carbonate, hexamethylene carbonate, and the like.
[0076] The number average molecular weight of the first polycarbonate polyol is preferably 500 to 10,000. More preferably, it is 700 to 8,000. When the number average molecular weight is 500 or more, the incompatibility with the domain containing the polyether of the second structural unit represented by formula (2) is ensured, and the phase separation between the matrix and the domain can be made clearer. In addition, by making the number average molecular weight 10,000 or less, an excessive increase in viscosity of the first polycarbonate polyol can be prevented.
[0077] The second polycarbonate polyol used in step (ii) may be any of the polycarbonate polyols listed in the first polycarbonate polyol. As described above, the first polycarbonate polyol and the second polycarbonate polyol may have the same chemical composition, or may be different from each other.
[0078] The polyisocyanate 56 having at least two isocyanate groups used in step (iii) may be the same as the polyisocyanates exemplified above as the raw material for the first polyether. These polyisocyanates may be used alone or in combination of two or more kinds. From the viewpoint of increasing the elastic modulus of the matrix, it is preferable that the polyisocyanate 56 includes a polyisocyanate having at least three isocyanate groups, such as a polyisocyanate trimer compound (isocyanurate) or polymer compound, an allophanate type polyisocyanate, or a biuret type polyisocyanate, among the polyisocyanates exemplified above. More preferably, the resin contains at least one selected from the group consisting of a trimer compound (isocyanurate) of pentamethylene diisocyanate, a trimer compound (isocyanurate) of hexamethylene diisocyanate, a polymeric compound of diphenylmethane diisocyanate, and polymeric MDI.
[0079] Among the above, polymeric MDI is preferred. Polymeric MDI is a mixture of monomeric MDI and high molecular weight polyisocyanate, and is represented by the following formula (A). n in formula (A) is preferably 0 or more and 4 or less. As the polymeric MDI, commercially available products may be used, and examples thereof include Millionate MR series (manufactured by Tosoh Corporation), such as Millionate MR200 (product name). [ka]
[0080] As the polyisocyanate 56 having at least two isocyanate groups, it is preferable to use a polyisocyanate having at least three isocyanate groups such as polymeric MDI in combination with a bifunctional isocyanate having two isocyanate groups. The combination of these is preferable from the viewpoint of achieving both low hardness and low compression set, since the crosslink density of the matrix can be adjusted by using these in combination.
[0081] The catalyst may be a conventional urethane catalyst or an isocyanurate catalyst (isocyanate). These may be used alone or in combination. Examples of the urethanization catalyst include tin-based urethanization catalysts such as dibutyltin dilaurate and stannous octoate, and amine-based urethanization catalysts such as triethylenediamine, tetramethylguanidine, pentamethyldiethylenetriamine, diethylimidazole, tetramethylpropanediamine, N,N,N'-trimethylaminoethylethanolamine, 1,4-diazabicyclo[2.2.2]octane-2-methanol, and N,N-dimethylaminohexanol. These may be used alone or in combination. Among these, N,N-dimethylaminohexanol is particularly preferred for obtaining the polyurethane elastomer according to the present disclosure. That is, 1,4-diazabicyclo[2.2.2]octane-2-methanol and N,N-dimethylaminohexanol have hydroxyl groups that can react with isocyanates to reduce amine emissions. Here, it is believed that when the hydroxyl groups react with isocyanates, the urethanization catalytic activity of the amine segments decreases. That is, it is believed that the higher the reactivity of the hydroxyl group with isocyanate, the lower the activity as a urethanization catalyst. And, compared to 1,4-diazabicyclo[2.2.2]octane-2-methanol, N,N-dimethylaminohexanol has a lower reactivity of the hydroxyl group with isocyanate, and it is believed that the urethanization catalyst activity is relatively less likely to decrease when used in a urethanization reaction. Therefore, in the step (i), it is possible to more effectively react the first polyether 51 having at least two isocyanate groups with the first polycarbonate polyol 52 having at least two hydroxyl groups. As a result, in the polyurethane elastomer obtained as a result of the above step (iii), the number of urethane bonds at the boundary between the domain and the matrix can be increased compared to the case where 1,4-diazabicyclo[2.2.2]octane-2-methanol is used as a catalyst. Therefore, the use of N,N-dimethylaminohexanol as a catalyst can further suppress the exudation of the domain components to the surface of the molded polyurethane elastomer, and is extremely effective in keeping the D / C within the range of 1.0 to 5.0.
[0082] In the present disclosure, in order to suppress the amount D of exudation onto the surface of the polyurethane elastomer molded body and adjust D / C to within the range of 1.0 to 5.0, as described above, A polyether polyol having two hydroxyl groups and a polyether polyol having three hydroxyl groups are used in combination as a raw material for the first polyether; and using N,N-dimethylaminohexanol as a catalyst; It is effective to adopt at least one selected from the group consisting of:
[0083] Examples of isocyanurate catalysts include metal oxides such as Li2O and (Bu3Sn)2O; hydride compounds such as NaBH4; alkoxide compounds such as NaOCH3, KO-(t-Bu), and borates; amine compounds such as N(C2H5)3, N(CH3)2CH2C2H5, and 1,4-ethylenepiperazine (DABCO); alkaline carboxylate salt compounds such as HCOONa, Na2CO3, PhCOONa / DMF, CH3COOK, (CH3COO)2Ca, alkali soap, and naphthenates; alkaline formate compounds; and quaternary ammonium salt compounds such as ((R)3-NR'OH)-OCOR". In this formula, Bu represents a butyl group, Ph represents a phenyl group, and R, R', and R" represent any alkyl group. In addition, examples of the combined catalyst (cocatalyst) used as the isocyanurate catalyst include amine / epoxide, amine / carboxylic acid, amine / alkyleneimide, etc. These isocyanurate catalysts and combined catalysts may be used alone or in combination.
[0084] In the production method of polyurethane elastomer, a chain extender (a low polyfunctional A chain extender may be used, for example, a glycol having a number average molecular weight of 1000 or less. Examples of glycols include ethylene glycol (EG), diethylene glycol (DEG), propylene glycol (PG), dipropylene glycol (DPG), 1,4-butanediol (1,4-BD), 1,6-hexanediol (1,6-HD), 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, xylylene glycol (terephthalyl alcohol), and triethylene glycol. Examples of chain extenders other than glycols include polyhydric alcohols having a valence of three or more. Examples of polyhydric alcohols having a valence of three or more include trimethylolpropane, glycerin, pentaerythritol, and sorbitol. These may be used alone or in combination. If necessary, additives such as foaming agents, microballoons, pigments, plasticizers, waterproofing agents, antioxidants, conductive agents, ultraviolet absorbing agents, and light stabilizers may also be used in combination.
[0085] The polyurethane molded article includes a polyurethane elastomer. For example, a polyurethane elastomer that has been heat-cured can be used as the polyurethane molded article as it is. The polyurethane molded article may have a foamed structure obtained by foaming using a mechanical froth method, a chemical foaming agent, or by adding microballoons. In addition, the polyurethane molded article can be applied to artificial muscles, artificial skin, synthetic leather, robot chucks, shoe soles, insoles, CMP polishing pads, stretchable electronics, flexible electronics, pressure sensors, stretch sensors, soft actuators, power generation elements, speakers, small pumps, etc. EXAMPLES
[0086] An embodiment of the present disclosure will be described in more detail below with reference to examples. However, the present disclosure is not limited to the following examples.
[0087] <Materials used> The materials used in the examples and comparative examples are listed below. [Polyol] [Table 1]
[0088] In the table, Kuraray Polyol C-2090 (manufactured by Kuraray Co., Ltd.) is a polycarbonate polyol having a number average molecular weight of 2000, a hydroxyl value of 56.3 mgKOH / g, and a structure corresponding to 1,6-hexanediol and a structure corresponding to 3-methyl-1,5-pentanediol. 1 contains a linear carbon atom number 6 structure and a branched carbon atom number 6 structure. Kuraray Polyol P-2050 is a polyester polyol having a structure corresponding to adipic acid and a structure corresponding to 3-methyl-1,5-pentanediol. PREMINOL S3011, Actocol EP-950N, and PREMINOL 7012 are all triol-type polypropylene glycols.
[0089] [Polyisocyanate] B-1: Xylylene diisocyanate (Tokyo Chemical Industry Co., Ltd.) B-2: Polymeric MDI (product name: Millionate MR-200, manufactured by Tosoh Corporation) [Curing catalyst] C-1: N,N-Dimethylaminohexanol (product name: Kao Raiser No. 25, manufactured by Kao Corporation) C-2: 1,4-diazabicyclo[2.2.2]octane-2-methanol (product name: RZETA, manufactured by Tosoh Corporation)
[0090] <Evaluation> The evaluation methods used in the examples and comparative examples are described below. [Evaluation 1: Confirmation of matrix domain and component analysis] A section was prepared from the polyurethane elastomer using a microtome, and a first molded body having a cubic shape with a side length of 100 μm was obtained. Then, mapping measurement was performed using a three-dimensional microscopic laser Raman spectroscopic analyzer (product name: Nanofinder 30, manufactured by Tokyo Instruments Co., Ltd.). The measurement mode was EM (Electron Multiplying), and measurements were made at 60 × 60 points at 500 nm intervals, and the area from 0 to 400 cm was measured. -1 The integral image was obtained. It was confirmed that the elastic layer contained a matrix and multiple domains dispersed in the matrix. The matrix and domains were clearly phase-separated. Next, the Raman spectrum of the matrix and domain parts was measured from the integral image. The measurement was performed with a light source of Nd:YVO4 (wavelength 532 nm), laser intensity of 240 μW, objective lens of 100x, diffraction grating of 300 gr / mm, pinhole diameter of 100 μm, exposure time of 30 seconds, and one integration. From the obtained Raman spectrum, it was confirmed that the matrix contains a structure derived from polycarbonate urethane, and the domain contains a structure derived from polypropylene glycol.
[0091] [Evaluation 2: Number of domains, equivalent sphere diameter, total volume ratio] First, a first molded body having a cubic shape with a side length of 100 μm was obtained in the same manner as in Evaluation 1. A three-dimensional stereoscopic image of the first molded body was obtained at intervals of 60 nm using a FIB-SEM (manufactured by FEI, Inc.). Then, the number N of domains, the arithmetic mean value Da of the sphere-equivalent diameters of the domains, and the ratio V of the total volume of the domains in the first molded body were calculated for the obtained images using 3D visualization and analysis software Avizo (registered trademark, manufactured by FEI, Inc.).
[0092] [Evaluation 3: Measurement of parameters indicating viscoelasticity] First, a first molded body having a cubic shape with one side of 100 μm was obtained in the same manner as in Evaluation 1. A section was prepared from the first molded body using a microtome. Then, a viscoelastic image was measured using a scanning probe microscope (product name: S-Image, manufactured by SII NanoTechnology Inc.). The measurement mode for the viscoelastic image was VE-DFM. In addition, the cantilever used was "SI-DF3" (product name, manufactured by Hitachi High-Tech Science Corporation, spring constant = 1.9 N / m). Furthermore, the scanning frequency was 0.5 Hz. From the obtained viscoelastic images, parameters indicating the viscoelastic term in each observation region were calculated for 10 points each for the matrix and domain, and parameter A (mV) indicating the viscoelastic term of the domain and parameter B (mV) indicating the viscoelastic term of the matrix were obtained from the arithmetic mean values.
[0093] [Evaluation 4: Measurement of micro rubber hardness] First, a sheet-like polyurethane elastomer molded body having a thickness of 2 mm was cut with scissors to obtain a second molded body having a cubic shape with each side measuring 2 mm. The micro rubber hardness of the second molded body was measured using a micro rubber hardness tester (product name: MD-1capa, manufactured by Kobunshi Keiki Co., Ltd.). For the measurement, the second molded body was left in an environment at a temperature of 23°C for 24 hours or more, and the measurement was performed using a measuring device placed in the same environment. In addition, a type A indenter (height 0.50 mm, diameter 0.16 mm, cylindrical, outer diameter 4 mm, inner diameter 1.5 mm) was used, and the measurement mode was peak hold mode.
[0094] [Evaluation 5: Measurement of recovery from deformation] First, a sheet-like polyurethane elastomer molded body having a thickness of 2 mm was cut with scissors to obtain a second molded body having a cubic shape with each side measuring 2 mm. The measurement point was set at approximately the center of any one surface of the second compact, and a nanoindenter (product name: Fischerscope HM2000, manufactured by Fisher Instruments Co., Ltd., a Vickers indenter with a square pyramid shape and a facing angle of 136°) was used to perform an indentation test at a temperature of 23°C. The Vickers indenter was pressed into the second compact at a loading rate of 10 mN / 30 seconds, and the load of 10 mN was maintained for 60 seconds. Thereafter, the load was removed at 10 mN / 30 seconds, and the strain value 5 seconds after the load was removed was measured to measure the recovery from deformation.
[0095] [Evaluation 6: Measurement of solvent extraction rate C] First, a mold for preparing a 2 mm thick sheet was used to prepare a sheet-like polyurethane elastomer molded body having a thickness of 2 mm. The sheet was cut with scissors to a length of 25 mm, a width of 10 mm, and a thickness of 2 mm to obtain a third molded body. In accordance with Japanese Industrial Standards (JIS) K6229:2015, the third molded body was subjected to Soxhlet extraction using acetone as an extraction solvent at an extraction temperature of 80°C and an extraction time of 4 hours. The ratio of the mass of the obtained extract E1 to the mass of the third molded body was calculated as the solvent extraction rate C (mass%).
[0096] [Evaluation 7: Measurement of the solvent extraction rate D of powder] First, a sheet-like polyurethane elastomer molded body with a thickness of 2 mm was cut with scissors to a length of 25 mm, a width of 10 mm, and a thickness of 2 mm to obtain a third molded body. The third molded body was sandwiched between two sheets of Kiriyama funnel filter paper 5B, which was then sandwiched between two degreased aluminum sheets, and pressed and pulverized at 10 MPa for 1 minute using a 50-ton press machine (product name: PEF 5041, manufactured by Kansai Roll Co., Ltd.) preheated to 130°C to obtain a powder. To determine the size of the powder, the particle size distribution was measured using a laser diffraction / scattering type particle size distribution analyzer (product name: Partica LA-960V2, manufactured by Horiba, Ltd.) equipped with a dry measurement unit, and the particle size showing the maximum peak (mode diameter) was determined. In addition, the two sheets of Kiriyama funnel filter paper holding the crushed third compact were folded and placed in a Soxhlet cylindrical filter paper, and extract E2 was obtained in the same manner as the solvent extraction rate C above, and the solvent extraction rate D (mass%) of the powder was calculated.
[0097] [Evaluation 8: Measurement of number average molecular weight of extract E2] Extract E2 obtained by solvent extraction of the powder was collected, dissolved in THF, and measured using the following measuring device and under the following measuring conditions. Measuring equipment: HLC-8320GPC (product name, manufactured by Tosoh Corporation) Column: TSKgel SuperMultiporeHZ-N (product name, manufactured by Tosoh Corporation) x 2 Solvent: THF Temperature: 40℃ Flow rate: 0.35mL / min
[0098] Measurements were performed using an RI (refractive index) detector as a detector. In addition, a calibration curve was created using the following materials as standard samples for creating a calibration curve. TSK standard polystyrene (product names "A-1000", "A-2500", "A-5000", "F-1", "F-2", "F-4", "F-10", "F-20", "F-40", "F-80", "F-128", manufactured by Tosoh Corporation). Based on this calibration curve, the number average molecular weight of extract E2 was calculated from the retention time of the obtained measurement sample.
[0099] [Evaluation 9: Measurement of viscosity of extract E2] 10 μL of extract E2 obtained in the measurement of the powder solvent extraction rate D was collected. Then, the viscosity of the collected extract E2 was measured at a measurement temperature of 25° C. and a shear rate of 1 (1 / s) using an ultra-micro sample viscometer (product name: m-VROC, manufactured by Rheosens Inc.), and this was taken as the viscosity of extract E2.
[0100] [Evaluation 10: Measurement of wear resistance] The wear resistance of the surface in the thickness direction of a sheet-like wear test piece made of polyurethane elastomer, measuring 30 mm in length, 30 mm in width, and 2 mm in thickness, was measured using a ball-on-disk friction and wear tester (product name: HEIDON Type: 20, manufactured by Shinto Chemical Industry Co., Ltd.) in accordance with JIS R1613:2010 under the following conditions (1) to (6). (1) Ball Material: Stainless steel Diameter: 10mm (2) Load: 100g (3)Environment: Temperature 23℃, 50%RH (4) Time: 60 minutes (5) Sliding circle diameter: 10 mm (6) Rotation speed of the disk on which the test specimen is placed: 300 rpm.
[0101] The wear test was carried out as follows. First, the mass of the wear test piece was measured. Next, the wear test piece was fixed with double-sided tape so that the center of the wear test piece was located approximately at the center of the sliding disk of a ball-on-disk friction wear tester (product name: HEIDON Type: 20, manufactured by Shinto Chemical Co., Ltd.). At this time, the surface in the thickness direction of the wear test piece was arranged so as to be in contact with the sliding disk. Next, the indenter made of the above-mentioned ball was pressed against the center of the wear test piece with a load of 100 g, and the wear test piece was rotated and slid for 60 minutes with a sliding circle diameter of 10 mm and a rotation speed of 300 rpm. After 60 minutes, the test piece was stopped, the wear powder and the double-sided tape were removed, and the mass of the test piece was measured. The mass reduction rate (mass%) was calculated from the mass of the test piece before and after the wear test.
[0102] [Example 1] <Preparation example of urethane prepolymer UP1> 21.5 parts by mass of polyol A-1 as a polyether polyol (first polyol) having at least two hydroxyl groups and a second structure represented by formula (2), 0.4 parts by mass of polyisocyanate B-1 as a first polyisocyanate, and 500 ppm of curing catalyst C-1 were mixed and heated at a temperature of 100° C. for 24 hours to synthesize a polyol (first polyether) having at least two isocyanate groups. 50.2 parts by mass of polyol A-4 as a third polyol (first polycarbonate polyol) was mixed therein and heated at a temperature of 100° C. for 4 hours to produce a urethane prepolymer (urethane reactive emulsifier) UP1 (step (i)).
[0103] <Production example of urethane elastomer molding No. 1> 72.1 parts by mass of urethane prepolymer UP1, 2.2 parts by mass of B-1 as the second polyisocyanate, and 3.8 parts by mass of B-2 as the third polyisocyanate were mixed, and the mixture was stirred for 2 minutes until it became homogeneous using a self-rotating vacuum stirring and degassing mixer (product name: V-mini300, manufactured by EME) at a revolution speed of 1600 rpm (steps (ii) and (iii)). Thus, a polyurethane elastomer forming mixture according to this embodiment was obtained. Next, the polyurethane elastomer forming mixture was preheated to a temperature of 130°C, poured into a mold for producing a 2 mm thick sheet on which a release agent was thinly applied, and heated at a temperature of 130°C for 2 hours to be cured (step (iii)). Next, the cured product was demolded and post-cured at a temperature of 80°C for 2 days to obtain a sheet-like polyurethane elastomer molded body No. 1 having a thickness of 2 mm.
[0104] [Example 2] <Preparation example of urethane prepolymer UP2> 15.0 parts by mass of polyol A-1 as the first polyol, 6.4 parts by mass of polyol A-7 as the second polyol, 0.5 parts by mass of polyisocyanate B-1 as the first polyisocyanate, and 500 ppm of curing catalyst C-1 were uniformly mixed and heated at a temperature of 100° C. for 24 hours to synthesize a polyol (first polyether) having an isocyanate group at its end. 50.2 parts by mass of polyol A-4 as the third polyol (first polycarbonate polyol) was mixed therein and heated at a temperature of 100° C. for 4 hours to produce a urethane prepolymer (urethane reactive emulsifier) UP2 (step (i)).
[0105] <Production example of urethane elastomer molding No. 2> Polyurethane elastomer molding No. 2 was obtained in the same manner as in Example 1, except that 72.1 parts by mass of the urethane prepolymer UP2, 2.1 parts by mass of B-1 as the second polyisocyanate, and 3.8 parts by mass of B-2 as the third polyisocyanate were used.
[0106] [Examples 3 and 4] Polyurethane elastomer molded body No. 3 and polyurethane elastomer molded body No. 4 were produced in the same manner as in Example 2, except that the materials shown in Table 2 were used in the amounts shown in Table 2.
[0107] [Examples 5 to 9, Comparative Examples 1 and 2] Polyurethane elastomer molded bodies Nos. 5 to 9 and polyurethane elastomer molded bodies Nos. C1 and C2 were produced in the same manner as in Example 1, except that the materials shown in Table 2 were used in the amounts shown in Table 2.
[0108] [Comparative Example 3] <Production example of urethane elastomer molding No. C3> 87.8 parts by mass of polyol A-5 as the first polyol, 4.9 parts by mass of B-1 as the first polyisocyanate, 7.3 parts by mass of B-2 as the second polyisocyanate, and 500 ppm of curing catalyst C-1 were mixed, and stirred for 2 minutes until homogeneous using a self-rotating vacuum stirring defoaming mixer at a revolution speed of 1600 rpm to obtain a polyurethane elastomer forming mixture. Next, a polyurethane elastomer molding No. C3 was obtained in the same manner as in Example 1, except that this polyurethane elastomer forming mixture was used.
[0109] [Comparative Example 4] <Production example of urethane elastomer molding No. C4> 23.5 parts by mass of polyol A-2 as the first polyol, 43.6 parts by mass of polyol A-6 as the second polyol, 3.8 parts by mass of B-1 as the first polyisocyanate, 5.7 parts by mass of B-2 as the second polyisocyanate, and 500 ppm of curing catalyst C-1 were mixed, and stirred for 2 minutes until homogeneous using a self-revolving vacuum stirring defoaming mixer at a revolution speed of 1600 rpm to obtain a polyurethane elastomer forming mixture. Next, a polyurethane elastomer molding No. C4 was obtained in the same manner as in Example 1, except that this polyurethane elastomer forming mixture was used. [Table 2] [Table 3]
[0110] Table 4 shows the evaluation results of the polyurethane elastomers according to Examples 1 to 9 and Comparative Examples 1 to 4. [Table 4] In the table, PPG represents a structure derived from polypropylene glycol, PTMG represents a structure derived from polytetramethylene glycol, PC represents a structure derived from polycarbonate urethane, PE represents a structure derived from polyester urethane, and F3 represents an addition polymer of glycerin and at least one selected from the group consisting of ethylene oxide and propylene oxide.
[0111] The polyurethane elastomer molding No. 1 according to Example 1 had a significantly reduced solvent extraction rate D of the pulverized material compared to the polyurethane elastomer molding No. C1 obtained in Comparative Example 1, which was different only in the catalyst used. The polyurethane elastomer molding No. C2 obtained in Comparative Example 2, which used a larger amount of catalyst than in Comparative Example 1, showed an improvement in the solvent extraction rate D of the pulverized material, but the micro rubber hardness increased. The polyurethane elastomer moldings No. C3 and C4 obtained in Comparative Examples 3 and 4, which did not have a domain structure, had a D / C close to 1, but showed a significantly reduced abrasion resistance compared to Example 1 and the like.
[0112] In addition, the polyurethane elastomer molded body No. 2 according to Example 2 and the polyurethane elastomer molded body No. 3 according to Example 3 further have a structure in the domain which is an addition polymer of glycerin and at least one selected from the group consisting of ethylene oxide and propylene oxide. Therefore, the number of urethane bonds at the boundary between the matrix and the domains is increased by the three-branched structure derived from glycerin, and thus it is possible to further suppress the exudation of components derived from the domains to the surface of the polyurethane elastomer molded body. The polyurethane elastomer molded body No. 4 according to Example 4 uses the same curing catalyst as in Comparative Example 1, but further has a structure in the domain which is an addition polymer of glycerin and at least one selected from the group consisting of ethylene oxide and propylene oxide. As a result, the solvent extraction rate D of the powder can be made equivalent to that of Example 1.
[0113] The present disclosure relates to the following configurations. [Configuration 1] A polyurethane elastomer having a matrix and a plurality of domains dispersed in the matrix, In a first molded body made of the polyurethane elastomer and having a cubic shape with each side measuring 100 μm, The number N of the included domains is 10 to 77,000, the arithmetic average value Da of the equivalent sphere diameter of the domains is 1.0 to 30.0 μm; a ratio V of the total volume of the domain in the first molded body is 15 to 45 volume %, The relationship between a parameter A indicating the viscoelastic term of the domain and a parameter B indicating the viscoelastic term of the matrix, which is measured in a viscoelastic image by a scanning probe microscope of a cut section parallel to one surface of the first molded body, is as follows: A <Bであり、 The second molded body made of the polyurethane elastomer has a micro rubber hardness of 20 to 50 degrees at a temperature of 23°C, and In an indentation test of the second compact using a nanoindenter at a temperature of 23°C, a Vickers indenter is pressed into the second compact at a loading rate of 10 mN / 30 seconds, the load of 10 mN is maintained for 60 seconds, and then the load is released. The strain 5 seconds after the load is released is 1.0 μm or less. The third molded product made of the polyurethane elastomer is subjected to Soxhlet extraction in accordance with Japanese Industrial Standards (JIS) K6229:2015 using acetone as an extraction solvent at an extraction temperature of 80°C for an extraction time of 4 hours, and the ratio of the mass of the obtained extract E1 to the mass of the third molded product is defined as C (mass%); The powder of the third molded body having a mode diameter of less than 1 μm was subjected to Soxhlet extraction in accordance with Japanese Industrial Standards (JIS) K6229:2015 using acetone as an extraction solvent at an extraction temperature of 80° C. for an extraction time of 4 hours. The ratio of the mass of the obtained extract E2 to the mass of the powder was A polyurethane elastomer characterized in that, when the mass ratio is D (mass %), D / C is 1.0 to 5.0. [Configuration 2] The polyurethane elastomer according to claim 1, wherein the number average molecular weight of the extract E2 is 2,000 to 100,000. [Configuration 3] 3. The polyurethane elastomer according to claim 1 or 2, wherein the viscosity of the extract E2 is 10,000 mPa·s or less. [Configuration 4] The polyurethane elastomer is A polyurethane elastomer according to any one of configurations 1 to 3, having a first structure represented by the following formula (1) and a second structure represented by the following formula (2), the matrix containing the first structure, and the domain containing the second structure: TIFF2025032984000008.tif26170 (In formula (1), R 1 represents an alkylene group having 3 to 12 carbon atoms. TIFF2025032984000009.tif16170 (In formula (2), R 2represents an alkylene group having 3 to 6 carbon atoms. [Configuration 5] the domain has a third structure, The polyurethane elastomer according to configuration 4, wherein the third structure is an addition polymer of glycerin and at least one selected from the group consisting of ethylene oxide and propylene oxide. [Configuration 6] A polyurethane elastomer according to any one of configurations 1 to 5, wherein a mass loss rate of a sheet-like abrasion test piece made of the polyurethane elastomer and having a length of 30 mm, a width of 30 mm, and a thickness of 2 mm is 10.0% by mass or less when a ball-on-disk abrasion test in accordance with JIS R1613:2010 is performed on a surface in the thickness direction under the following conditions (1) to (6): (1) Ball Material: Stainless steel Diameter: 10mm (2) Load: 100g (3)Environment: Temperature 23℃, 50%RH (4) Time: 60 minutes (5) Sliding circle diameter: 10 mm (6) Rotation speed of the disk on which the wear test piece was placed: 300 rpm. [Configuration 7] A polyurethane molded product comprising the polyurethane elastomer according to any one of aspects 1 to 6. [Configuration 8] 8. The polyurethane molded article according to claim 7, wherein the polyurethane molded article has a foamed structure. [Explanation of symbols]
[0114] 3: polyurethane molding, 31: matrix, 32: domain
Claims
1. A polyurethane elastomer having a matrix and a plurality of domains dispersed in the matrix, In a first molded body made of the polyurethane elastomer and having a cubic shape with each side measuring 100 μm, The number N of the included domains is 10 to 77,000; the arithmetic average value Da of the equivalent sphere diameter of the domain is 1.0 to 30.0 μm; a ratio V of the total volume of the domain in the first molded body is 15 to 45 volume %, a relationship between a parameter A indicating a viscoelastic term of the domain and a parameter B indicating a viscoelastic term of the matrix, which are measured in a viscoelastic image by a scanning probe microscope of a cut section parallel to one surface of the first molded body, is A<B; The second molded body made of the polyurethane elastomer has a micro rubber hardness of 20 to 50 degrees at a temperature of 23°C, and In an indentation test using a nanoindenter at a temperature of 23°C, a Vickers indenter was pressed into the second compact at a loading rate of 10 mN / 30 seconds, the load of 10 mN was maintained for 60 seconds, and then the load was removed. The strain 5 seconds after removal of the load was 1.0 µm or less. The third molded article made of the polyurethane elastomer is subjected to Soxhlet extraction in accordance with Japanese Industrial Standards (JIS) K6229:2015 using acetone as an extraction solvent at an extraction temperature of 80° C. for an extraction time of 4 hours. The ratio of the mass of the obtained extract E1 to the mass of the third molded article is defined as C (mass%), When powder of the third molded body having a mode diameter of less than 1 μm is subjected to Soxhlet extraction in accordance with Japanese Industrial Standards (JIS) K6229:2015 using acetone as an extraction solvent at an extraction temperature of 80° C. for an extraction time of 4 hours, the ratio of the mass of the obtained extract E2 to the mass of the powder, D / C, is 1.0 to 5.0 (mass%).
2. The polyurethane elastomer according to claim 1, wherein the number average molecular weight of the extract E2 is 2,000 to 100,000.
3. The polyurethane elastomer according to claim 1, wherein the viscosity of the extract E2 is 10,000 mPa·s or less.
4. The polyurethane elastomer is The polyurethane elastomer according to claim 1, comprising a first structure represented by the following formula (1) and a second structure represented by the following formula (2), the matrix containing the first structure, and the domain containing the second structure: (In formula (1), R 1 represents an alkylene group having 3 to 12 carbon atoms. (In formula (2), R 2 represents an alkylene group having 3 to 6 carbon atoms.
5. the domain has a third structure, The polyurethane elastomer according to claim 4, wherein the third structure is an addition polymer of glycerin and at least one selected from the group consisting of ethylene oxide and propylene oxide.
6. The polyurethane elastomer according to claim 1, wherein a mass loss rate of a sheet-like abrasion test piece made of the polyurethane elastomer and having a length of 30 mm, a width of 30 mm, and a thickness of 2 mm is 10.0% by mass or less when a ball-on-disk abrasion test in accordance with JIS R1613:2010 is performed on a surface in the thickness direction under the following conditions (1) to (6): (1) Ball Material: Stainless steel Diameter: 10mm (2) Load: 100g (3) Environment: Temperature 23℃, 50%RH (4) Time: 60 minutes (5) Sliding circle diameter: 10 mm (6) Rotation speed of the disk on which the wear test piece was placed: 300 rpm.
7. A polyurethane molding comprising the polyurethane elastomer according to any one of claims 1 to 6.
8. The polyurethane molded article according to claim 7, which has a foamed structure.
Citation Information
Patent Citations
Polyurethane elastomer and production method thereof
JP2022168829A